2015
DOI: 10.5812/jjm.25368
|View full text |Cite
|
Sign up to set email alerts
|

Torque Teno Midi Virus/Small Anellovirus in Sera of Healthy, HIV/HCV and HIV Infected Individuals in Lorestan Province, Iran

Abstract: Background:Torque Teno Midi Virus/Small Anellovirus (TTMDV/SAV) is a member of the Gammatorquevirus genus within the family Anelloviridae. It is detected in healthy, Hepatitis B Virus, Hepatitis C Virus and HIV infected individuals and also patients with acute respiratory disease in different countries, but its role in clinical diseases and its full geographical distribution is still unclear.Objectives:The current study aimed to detect the frequency of infection with TTMDV/SAV in the sera of healthy blood dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
8
1
1
Order By: Relevance
“…With regards to TTMDV, the viremia frequency of the virus in healthy individuals was 14.5% in Iran [19], 34.5% in Korea [27], 20% in France [27], and 8.6% in Italian blood donors [18]. Those findings are much lower than the 74.6% reported in the current study in Qatar.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…With regards to TTMDV, the viremia frequency of the virus in healthy individuals was 14.5% in Iran [19], 34.5% in Korea [27], 20% in France [27], and 8.6% in Italian blood donors [18]. Those findings are much lower than the 74.6% reported in the current study in Qatar.…”
Section: Discussioncontrasting
confidence: 69%
“…Further, Garcia-Alvarez et al reported a very high incidence rate of TTV and TTMV in HIV/HCV-coinfected patients, which is higher than the 83% infection rate in HCV patients in the current study [28]. Also, in another study in Iran, researchers reported a TTMDV incidence rate of 80.5% (29/36) and 75% (3/4) in HIV/HCV and HIV/HCV/HBV coinfected patients, respectively [19], which was lower than the 88.7 and 98.1% TTMDV infection rates obtained in HCV and HBV infected patients in the current study (Table 2). …”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…HPgV-1 RNA was detected in all groups tested (6.78%), whereas HPgV-2 RNA was restricted to the HCV-infected group (1.51%). Similarly, the presumably nonpathogenic and transfusion-transmitted anelloviruses have been detected in all of these groups, including healthy donors, and have distributions comparable to that of HPgV-1 ( 26 28 ). Thus, there is a notable dichotomy in which commensal viruses (anelloviruses and HPgV-1) are more prevalent across all populations, with HPgV-2 showing clear enrichment in populations coinfected with the pathogenic virus HCV.…”
Section: Discussionmentioning
confidence: 88%
“…Reports of TTMDV and TTMV prevalence are heterogeneous and data regarding prevalence in the blood of healthy individuals are scarce. For TTMDV, the prevalence ranges between 14.5% in Iran [ 3 ] and 75% in Japan [ 4 ], while the prevalence of TTMV varies between 29% in Korea [ 5 ] and 84.8% in Japan [ 4 ].…”
Section: Introductionmentioning
confidence: 99%